(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
A revision of the genus Smittia Holmgren (Diptera Chironomidae subfamily Orthocladiinae tribe Metriocnemini) is carried out. Three new species, S. abruzzae, S. alpilonga and S. stercoraria are here described, S. alpicola Goetghebuer, 1941 is redescribed from type materia!, S. rostrata Goetghebuer in Schmolzer, 1962, previously considered a nomen dubium, is redescribed from type materi al. Species descriptions are based on adult males morphology, at present no diagnostic character is available to separate adult females, pupae and larvae. A key to identify the known palearctic species is given.